Cigarette smoke alters the ability of human dendritic cells to promote anti-Streptococcus pneumoniae Th17 response. Issue 1 (December 2016) - Le Rouzic, Olivier; Koné, Bachirou; Kluza, Jerome; Marchetti, Philippe; Hennegrave, Florence; Olivier, Cécile; Kervoaze, Gwenola; Vilain, Eva; Mordacq, Clémence; Just, Nicolas; Perez, Thierry; Bautin, Nathalie; et al.
Abstract Background Chronic obstructive pulmonary disease (COPD) is associated with chronic inflammation and impaired immune response to pathogens leading to bacteria-induced exacerbation of the disease. A defect in Th17 cytokines in response toStreptococcus pneumoniae, a bacteria associated with COPD exacerbations, has been recently reported. Dendritic cells (DC) are professional antigen presenting cells that drive T-cells differentiation and activation. In this study, we hypothesized that exposure to cigarette smoke, the main risk factor of COPD, might altered the pro-Th17 response toS. pneumoniae in COPD patients and human DC. Methods Pro-Th1 and -Th17 cytokine production by peripheral blood mononuclear cells (PBMC) from COPD patients was analyzed and compared to those from smokers and non-smokers healthy subjects. The effect of cigarette smoke extract (CSE) was analyzed on human monocyte-derived DC (MDDC) from controls exposed or not toS. pneumoniae . Bacteria endocytosis, maturation of MDDC and secretion of cytokines were assessed by flow cytometry and ELISA, respectively. Implication of the oxidative stress was analyzed by addition of antioxidants and mitochondria inhibitors. In parallel, MDDC were cocultured with autologous T-cells to analyze the consequence on Th1 and Th17 cytokine production. Results PBMC from COPD patients exhibited defective production of IL-1β, IL-6, IL-12 and IL-23 toS. pneumoniae compared to healthy subjects and smokers. CSE significantly reducedS. pneumoniae -induced MDDC maturation, secretion of pro-Th1 and -Th17 cytokines and activation of Th1 and Th17 T-cell responses. CSE exposure was also associated with sustained CXCL8 secretion, bacteria endocytosis and mitochondrial oxidative stress. Antioxidants did not reverse these effects. Inhibitors of mitochondrial electron transport chain partly reproduced inhibition ofS. pneumoniae -induced MDDC maturation but had no effect on cytokine secretion and T cell activation. Conclusions We observed a defective pro-Th1 and -Th17 response to bacteria in COPD patients. CSE exposure was associated with an inhibition of DC capacity to activate antigen specific T-cell response, an effect that seems to be not only related to oxidative stress. These results suggest that new therapeutics boosting this response in DC may be helpful to improve treatment of COPD exacerbations.